(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this research was to use mathematical models to evaluate Tigris River water quality in the metropolitan area of Mosul (WQI). Starting in November 2021 and continuing through March 2022, researchers will collect 120 water samples from six different locations along the Mosul River before it enters the city of Mosul at Badush Kasbah, north-east of the city, all the way down to the Yarmajeh area, south of Mosul (at a rate of two repeats per month for each site) in order to conduct physical and chemical analyses. In addition, the water quality for irrigation was assessed using the (Sub-index-WQI) model and the Kelly Index, K.R., both of which adhere to internationally accepted standard techniques.According to the results of the study, majority of the standards utilized fell within the acceptable range for Irrigation as defined by (WHO, 2004), as shown by the values of the sub-index index falling somewhere in the (44.82-46.12). Because of this, the Tigris River in Mosul City has a high enough quality to be used for irrigation.